2015
DOI: 10.1117/1.jbo.20.3.030901
|View full text |Cite
|
Sign up to set email alerts
|

Review of short-wave infrared spectroscopy and imaging methods for biological tissue characterization

Abstract: Abstract. We present a review of short-wave infrared

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
241
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(246 citation statements)
references
References 49 publications
(124 reference statements)
4
241
0
1
Order By: Relevance
“…117,118 In addition, SWIR includes more absorption peaks, thereby adding additional information and hence improved sensitivity for various chromophores such as proteins, water, collagen, lipids, and so on. 116,119,120 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…117,118 In addition, SWIR includes more absorption peaks, thereby adding additional information and hence improved sensitivity for various chromophores such as proteins, water, collagen, lipids, and so on. 116,119,120 …”
Section: Resultsmentioning
confidence: 99%
“…Since each of the three systems possesses its own unique benefits and limitations, we suggest future study of a multimodal approach combining complementary imaging methods for their further optimization. Moreover, the implementation of longer wavelengths in the spectral range of 1000 to 2000 nm, known as short-wave infrared (SWIR), 116 will be considered in this proposed combined system. This region holds an important advantage for spectroscopy and imaging purposes: within this range, scattering is attenuated monotonically, leading to increased transparency of photons within the tissue and hence improved penetration depth.…”
Section: Resultsmentioning
confidence: 99%
“…However, recent investigations emphasize the advantage of high penetration depth and enhanced constituent specificity in the short wave infrared (SWIR) 1100-to 1700-nm range. [8][9][10] Importantly, the lack of systematic characterization of tissue constituents in the SWIR range prevents its widespread use for in vivo applications.…”
mentioning
confidence: 99%
“…Enhanced contrast of collagen absorption was reported using photoacoustics at SWIR wavelengths as compared to the near-infrared region. 15,16 For collagen, the high absorption in the SWIR region 9 can be exploited to investigate its dynamics of growth in studies related to tissue culture or engineering. 17,18 To our knowledge, the first characterization of collagen absorption in the 600-to 1100-nm range was reported by Taroni et al 19 in 2009 then followed by Nachabé et al 8 However, little information is available on the absolute absorption spectrum of collagen in the SWIR, despite all the interesting features of collagen in that range and the related potential diagnostic applications mentioned above.…”
mentioning
confidence: 99%
“…Thus, NIR and SWIR spectroscopy is useful and informative for distinguishing between different hydration levels in skin which is very interesting for the cosmetic industry, as well as for dermatologists. There are three main areas of research regarding diffuse reflectance spectroscopy in the NIR and SWIR spectral ranges: 1) integrating sphere based measurements for estimating ex vivo tissue absorption and scattering coefficients; 2) fiber probe based "point" measurements to acquire reflectance measurements collected over small localized tissue volumes both in vivo and ex vivo; 3) imaging measurements both in vivo [1][2] and ex vivo that offer non-contact measurements of a larger area of tissues [3]. Previous studies based on fiber probe reflectance spectroscopy method have shown NIR and SWIR spectroscopy applications for distinguishing between ex vivo vulnerable and stable atherosclerotic plaques by estimating lipid-to-protein ratios [4][5], as well as distinguishing between ex vivo normal and cancerous breast tissue by estimating water and lipid volume fractions [6].…”
Section: Near-infrared Reflectance Spectroscopymentioning
confidence: 99%